Einem anderen die Gewissensentscheidung bewusst überlassen: zur Phänomenologie einer spezifischen Verhaltensmöglichkeit - Witschen, Dieter (Zeitschrift für katholische Theologie, 2009)
Even though decisions of conscience are personal decisions of a subject and within its personal responsibility, there remains the question of the ethical implications of letting a subject make a decision of conscience. The author examines the implications of ceding the making of a decision of conscience and the circumstances under which such ceding can be judged ethically good.